Influence Analysis of Washers Material in the Fatigue Life of Bolted Joints - De Azevedo Silva, Fernando [UNESP]; Guidi, Erick Siqueira [UNESP] (My University, 2015)
The union of parts by using bolts is one of the most used, which combines versatility and low cost, and the failure of a single bolt can cause failure of the entire structure or machine. Several factors influence the effectiveness of these bolted joints, including the material of the washer. During the process of applying torque to the bolted joint, an elastic deformation occurs in the bolt and a plastic deformation in the washer while applying the external force. This plastic deformation which occurs in the washer causes a reduction of the elastic deformation of the bolt and, consequently, of the assembly torque, and depending on the values of external loading and deformation of the washer occurs the separation of the pieces of the joint, causing overload in the bolt and a reduction in your fatigue life. The use of numerical simulation using the finite element method makes it possible to change the model variables, such as the geometry and materials of the components.